Research progress in chronic kidney diseases and cardiovascular diseases - ZHU Yu-xing; BA Ying-gui (Linchuang shenzangbing zazhi)
As two important organs controlling the effective circulation and hemodynamics of the body, heart and kidney are interdependent in physiological function and influence each other in pathological state, and have much in common in treatment. Chronic kidney disease(CKD) is a common disease that seriously endangers human health and life. CKD is not only a high risk factor of end stage renal disease(ESRD), but also a high risk factor of cardiovascular and all-cause death. Therefore, the prevention and treatment objectives should not only slow down and control the progressive deterioration of renal function, but also prevent the occurrence and deterioration of cardiovascular disease(CVD), the main fatal complication. However, the pathogenesis, risk factors and treatment and prevention of CVD in CKD patients are very difficult and complex. This article reviews the pathogenesis, risk factors, treatment and prevention of CVD in CKD patients.